Nitrogênio em cobertura e molibdênio via foliar em feijoeiro de inverno no sistema plantio direto II - Características agronômicas e produtividade - Do Nascimento, Martha Santana [UNESP]; Arf, Orivaldo [UNESP]; Barbosa, Giselle Feliciani [UNESP]; Buzetti, Salatiér [UNESP]; Do Nascimento, Rildo Santana [UNESP]; Castro, Rodrigo Martinez [UNESP] (My University, 2009)
Nitrogen is the nutrient most uptaken by common bean plant, and molybdenum besides its importance to N fixation process, it is associated to N metabolism. The objective of this work was to evaluate, on common bean crop Pérola cultivar, the effect of N levels application at side dressing (0, 30, 60, 90 and 120 kg ha-1) as well as the leaf application of Mo (0, 80 and 160 g ha-1) at development stadium V3 or V4 under no tillage system. The experimental design was the randomized blocks with 30 treatments and 4 replications. The research was conducted in Selviria-MS on soil previously cropped with corn. The application of nitrogen levels at side dressing provided increasing on dry mass weight, number of pod and seeds per plant and grain yield, in the 2004; the Mo application at V3 or V4 stadia did not effect the production components and grain yield; as well as different doses of Mo depended on the N application at side dressing, in the 2004.
Side dressing nitrogen and leaf molybdenum application on winter common bean crop under no tillage system II - Agronomic characteristics and yield
Keywords: Application times; Mo fertilization; N fertilization; Phaseolus vulgaris